The Influence Of Endurance And Speed On The Mae Geri Jodan Kick In Terms Of Accuracy In Lemkari Athletes From Takalar Regency - Rizal Sukarman; Syahruddin; Rachmat Kasmad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to determine the effect of endurance and speed on mae geri jodan kicks in terms of accuracy of Lemkari athletes in Takalar Regency. The background of this study is based on the ability of mae geri jodan kicks in karate athletes who are still not good at doing kumite which becomes the basis for further research on the influences that affect the ability of karateka kicks. This study uses a path analysis approach from each variable on the ability to perform mae geri jodan kicks. The sample of this study amounted to 50 male karateka with green belts and above. The instruments used were the Coper minute test, accuracy test, and repetition test of mae geri jodan kicks. The results of this study indicate that the ability to kick mae geri is influenced by a combination of physical and technical factors, especially endurance, speed, and accuracy. The results of the t-test show that endurance has a significant effect on the ability to kick mae geri jodan, indicated by the calculated t value being greater than the t table at a significance level of 0.05. In addition, speed also shows a significant effect on the ability to kick mae geri with the calculated t value > t table.